Guidelines for safe automation of chemical processes. (Center for Chemical Process Safety of the American Institute of Chemical Engineers, 1993)
Increased automation reduces the potential for operator error, but introduces the possibility of new types of errors in design and maintenance. This book provides designers and operators of chemical process facilities with a general philosophy and approach to safe automation, including independent layers of safety.